2017
DOI: 10.1016/j.neuroscience.2016.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Time-course of glial changes in the hyperhomocysteinemia model of vascular cognitive impairment and dementia (VCID)

Abstract: Vascular cognitive impairment and dementia (VCID) is the second leading cause of dementia behind Alzheimer’s disease (AD) and is a frequent co-morbidity with AD. Despite its prevalence, little is known about the molecular mechanisms underlying the cognitive dysfunction resulting from cerebrovascular disease. Astrocytic end-feet almost completely surround intraparenchymal blood vessels in the brain and express a variety of channels and markers indicative of their specialized functions in the maintenance of ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
69
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 45 publications
10
69
3
Order By: Relevance
“…Significant disruptions of astrocytic end-foot function have been reported in many neurological conditions including ischemia (Frydenlund et al 2006), brain tumors (Saadoun et al 2003), epilepsy (Eid et al 2005), and brain contusion (Saadoun et al 2003). In the course of our own research, we have found similar astrocytic end-foot disruption in mouse models of AD, human AD with CAA, and a mouse model of VCID (Wilcock et al 2009;Sudduth et al 2017).…”
Section: Dementia-related Astrocytic End-foot Disruptionsupporting
confidence: 58%
See 2 more Smart Citations
“…Significant disruptions of astrocytic end-foot function have been reported in many neurological conditions including ischemia (Frydenlund et al 2006), brain tumors (Saadoun et al 2003), epilepsy (Eid et al 2005), and brain contusion (Saadoun et al 2003). In the course of our own research, we have found similar astrocytic end-foot disruption in mouse models of AD, human AD with CAA, and a mouse model of VCID (Wilcock et al 2009;Sudduth et al 2017).…”
Section: Dementia-related Astrocytic End-foot Disruptionsupporting
confidence: 58%
“…Although essential for interneuronal communication within the brain, glutamate can become a powerful excitotoxin if levels are not maintained within a particular range. Moreover, loss and/or disruption of endfeet, similar to that described above for VCID mouse models (Wilcock et al 2009;Sudduth et al 2017), are also found in disease models where excitotoxic damage is prominent (Alvestad et al 2013;Gondo et al 2014). Synapses are particularly vulnerable to excitotoxic insults and are lost at very early stages of cognitive decline associated with Alzheimer's disease.…”
Section: Glutamate Homeostasismentioning
confidence: 65%
See 1 more Smart Citation
“…If the NVC signaling cascade is impaired and cerebrovascular tone pathologically altered, local blood flow is compromised and neuronal dysfunction ensues. Cerebral blood flow is known to be disturbed both in neurodegenerative diseases (Alzheimer's disease and vascular dementia) and in a range of their risk factors (e.g., hypertension, stroke, and diabetes) (Arvanitakis et al 2016;Bogush et al 2017;Eskildsen et al 2017;Kelleher and Soiza 2013;Longden et al 2016;Love and Miners 2017;McInerney et al 2017;Nielsen et al 2017;Perrotta et al 2016;Sheen and Sheu 2016;Sudduth et al 2017). Moreover, brain imaging (via MRI) of human subjects (n=143) yielded results showing brain iron deposits significantly associated with general cognitive ability in old age and with age-related cognitive decline (Penke et al 2012).…”
Section: Targeting Senile Endothelium Brain Biometal (Fe Ca) Dyshommentioning
confidence: 99%
“…Small-vessel disease is commonly found in patients who have other brain pathologies, such as the plaques and tangles associated with neurodegenerative disease; small-vessel disease also increases the risk of Alzheimer's disease. In fact, vascular cognitive impairment and dementia (VCID) is the second leading cause of dementia behind Alzheimer's disease, and is a frequent comorbidity in the Alzheimer's patient (Cooper and Mitchell 2016;Dichgans and Leys 2017;Greenberg et al [for MarkVCID consortium] 2017;Kalaria 2016;Perrotta et al 2016;Sudduth et al 2017). On a worldwide basis, 36 million people had dementia in 2010; of these dementia patients, 60%-80% have Alzheimer's disease (Bhat et al 2015;Dichgans and Leys 2017;Manukhina et al 2016).…”
Section: Introductionmentioning
confidence: 99%